Overexpression of alpha2A-adrenergic receptors contributes to type 2 diabetes. - Rosengren, A; Jokubka, R; Tojjar, D; Granhall, C; Hansson, O; Li, D; Nagaraj, V; Reinbothe, T; Tuncel, J; Eliasson, L; Groop, L; Rorsman, P; et al. (2010)
Several common genetic variations have been associated with type 2 diabetes, but the exact disease mechanisms are still poorly elucidated. Using congenic strains from the diabetic Goto-Kakizaki rat, we identified a 1.4-megabase genomic locus that was linked to impaired insulin granule docking at the plasma membrane and reduced beta cell exocytosis. In this locus, Adra2a, encoding the alpha2A-adrenergic receptor [alpha(2A)AR], was significantly overexpressed. Alpha(2A)AR mediates adrenergic suppression of insulin secretion. Pharmacological receptor antagonism, silencing of receptor expression, or blockade of downstream effectors rescued insulin secretion in congenic islets. Furthermore, we identified a single-nucleotide polymorphism in the human ADRA2A gene for which risk allele carriers exhibited overexpression of alpha(2A)AR, reduced insulin secretion, and increased type 2 diabetes risk. Human pancreatic islets from risk allele carriers exhibited reduced granule docking and secreted less insulin in response to glucose; both effects were counteracted by pharmacological alpha(2A)AR antagonists.